Language and Reading Progress of Young Deaf and Hard-of-Hearing Children. (13th February 2020) - Antia, Shirin D; Lederberg, Amy R; Easterbrooks, Susan; Schick, Brenda; Branum-Martin, Lee; Connor, Carol M; Webb, Mi-Young
Abstract: We examined the language and reading progress of 336 young DHH children in kindergarten, first and second grades. Trained assessors tested children's language, reading, and spoken and fingerspelled phonological awareness in the fall and spring of the school year. Children were divided into groups based on their auditory access and classroom communication: a spoken-only group ( n  = 101), a sign-only group ( n  = 131), and a bimodal group ( n  = 104). Overall, children showed delays in language and reading compared to norms established for hearing children. For language, vocabulary standard scores were higher than for English syntax. Although delayed in language, children made expected gains based on hearing norms from kindergarten to second grade. Reading scores declined from kindergarten to second grade. Spoken-only and bimodal children had similar word reading and reading comprehension abilities and higher scores than sign-only children. Spoken-only children had better spoken phonological awareness and nonword reading skills than the other two groups. The sign-only and bimodal groups made similar and significant gains in ASL syntax and fingerspelling phonological awareness.